Otoriter Budaya Patriarki dalam Novel Azab dan Sengsara Karya Merari Siregar: Feminisme Eksistensialitas - Asia M, Asia M; Ridwan, Ridwan; Vanesa, Vanesa (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This research aims to examine the novel entitled "Azab dan sengsara" by Merari Siregar using the existential feminism approach as a view of the role of women in expressing their existentiality how women do not rely on men in their lives.  The method in this research uses descriptive qualitative through novel data sources by analyzing the existence of women in characters, and examining the influence of patriarchal culture on male characters. The results of the study discuss the conflicts that occur in a society by discussing the views of male characters, and the habits of society as a means of dominating women, such as, gender inequality, women's unfreedom in forced marriages, women's love results in discrimination In addition to this, it has been found that the existence of women in society, who are aware of the existence of women, and get the right to position as women including, the right to freedom, the right to express ideas and opinions, the right to be recognized.